An expanded immunohistochemical profile of osteoclast-rich undifferentiated carcinoma of the urinary tract. (June 2018) - Priore, Salvatore; Schwartz, Lauren; Epstein, Jonathan
Abstract Osteoclast-rich undifferentiated carcinoma of the urinary tract (ORUCUT) is a rare tumor composed of ovoid to spindle-shaped mononuclear cells with intermixed or focally clustered osteoclast-like giant cells. Previous studies have demonstrated that the mononuclear cells are neoplastic cells, while the giant cells are reactive cells of histiocytic lineage. The association between these tumors and classic urothelial carcinomas suggest that the mononuclear cells are derived from urothelial cells; however, no studies have been conducted to assess the immunohistochemical profile of ORUCUT with more specific urothelial markers. This study identified 21 cases of ORUCUT and performed immunohistochemistry for GATA3, uroplakin II, and thrombomodulin along with pancytokeratin (AE1/3) on all cases. Mononuclear cells stained positive in 20 cases (95%) for GATA3 and 19 cases (90%) for thrombomodulin. None of the mononuclear cells were positive for uroplakin II and only three cases showed focal positivity for AE1/3. The osteoclast-like giant cells were negative for GATA3, uroplakin II, thrombomodulin, and AE1/3, providing additional support to a reactive origin for these cells. Additionally, 15 cases (71%) were associated with either in situ or invasive urothelial carcinoma. This study provides an expanded immunohistochemical profile for ORUCUT and more definitively supports a urothelial origin for this tumor.